Answer:
m∠R > 90°
m∠S + m∠T < 90°
m∠R > m∠T
m∠R > m∠S
Explanation:
Here, RST is a triangle
Therefore, m∠R+m∠S+m∠T = 180° ⇒ m∠S+m∠T = 180° - m∠R
Given: m∠R > m∠S + m∠T
⇒ - m∠R < - (m∠S + m∠T) (by multiplying -1 on both sides)
⇒ 180° - m∠R < 180° - (m∠S + m∠T) (by adding 180° on both sides)
⇒ m∠S+m∠T < 180° - (m∠S + m∠T)
⇒ m∠S+m∠T+m∠S+m∠T < 180° (by adding m∠S + m∠T on both sides)
⇒ 2(m∠S+m∠T) < 180°
⇒ m∠S+m∠T < 90°
⇒ m∠R > 90° ( because m∠R+m∠S+m∠T=180° )
Again, m∠R > m∠S + m∠T
⇒ m∠R > m∠S and m∠R > m∠T
Thus, Option first, second, fourth and fifth are correct.